Effectiveness of Solar Panel-Based Street Lights and Their Impact on Environmental Sustainability - Arisman, Arisman; Iwan, Iwan (LifeSciFi, 2023)
Unlike conventional energy sources, solar lights provide access to sustainable lighting in areas not yet covered by the electricity grid. However, it is also important to carry out a detailed analysis of the energy effectiveness of using streetlights. The aim of this research is to analyze the difference in energy effectiveness between the use of conventional streetlights and solar panel-based streetlights. The research method used in this research is a field research method with a comparative approach. Field research is an approach that involves collecting data directly from the location or place where the phenomenon under study occurs. This research uses a comparative approach, where in this case the researcher compares the energy effectiveness between the two types of streetlights used, namely conventional streetlights in Andongsili Village and solar panel-based streetlights in Bumerto Village, both are in Central Java. The results of this research prove that solar panel-based streetlights have extraordinary energy effectiveness, converting sunlight into a sufficient resource for lighting throughout the night. The use of solar panel-based streetlights has a positive impact on the environment by reducing greenhouse gas emissions and dependence on fossil fuels. Additionally, in the context of remote villages that have limited electricity supplies, solar panel-based streetlights bring significant benefits in providing sustainable lighting. The use of solar panel-based streetlights provides significant financial benefits in the long term compared to conventional streetlights.